SETTLEMENT OF INTERNATIONAL INVESTMENT DISPUTES AND ITS MECHANISMS (World Bulletin of Management and Law, 2024)
Investment disputes usually arise between foreign investors and host countries when investment agreements or international law are violated. There are several reasons for international investment disputes, and these reasons are analyzed in the article. It is analyzed to what extent the occurrence of investment disputes affects the internal economy of the states, investors, global economy, and diplomatic relations. The factors of settlement of investment disputes are analyzed. Also, investment dispute resolution mechanisms and their pros and cons are explored. Concepts such as ISDS, FDI, BIT, TTIP, ICSID and LCIA will be covered during analysis and study. In addition, the Ukraine-Lithuania BIT, the case between Tokyo Tokelés and Lithuania will be considered. After conducting research in this field and analyzing it, proposals are made for the development of the field and elimination of the shortcomings that have arisen in the research